Ionized outflows in luminous type 2 AGNs at z < 0.6: no evidence for significant impact on the host galaxies. Issue 1 (17th April 2016) - Villar-Martín, M.; Arribas, S.; Emonts, B.; Humphrey, A.; Tadhunter, C.; Bessiere, P.; Cabrera Lavers, A.; Ramos Almeida, C.
Abstract: We investigate the presence of extended ionized outflows in 18 luminous type 2 AGNs (11 quasars and 7 high-luminosity Seyfert 2s) at 0.3 < z < 0.6 based on VLT-FORS2 spectroscopy. We infer typical lower limits on the radial sizes of the outflows R o ≳ several × 100 pc and upper limits R o ≲ 1–2 kpc. Our results are inconsistent with related studies which suggest that large scale ( R o ∼ several-15 kpc) are ubiquitous in QSO2. We study the possible causes of discrepancy and propose that seeing smearing is the cause of the large inferred sizes. The implications in our understanding of the feedback phenomenon are important since the mass M o (through the density), mass injection 3M_o and energy injection E_o rates of the outflows become highly uncertain. One conclusion seems unavoidable: M o, 3M_o and E_o are modest or low compared with previous estimations. We obtain typically M o ≲ (0.4–22) × 10 6 M⊙ (median 1.1 × 10 6 M⊙ ) assuming n = 1000 cm −3 . These are ∼10 2 –10 4 times lower than values reported in the literature. Even under the most favourable assumptions, we obtain 3M_o 10 M⊙ yr −1 in general, 100–1000 times lower than claimed in related studies. Although the uncertainties are large, it is probable that these are lower than typical star-forming rates. In conclusion, no evidence is found supporting that typical outflows can affect the interstellar medium of the host galaxies across spatial scales ≳ 1–2 kpc.